2018
DOI: 10.1116/1.5043550
|View full text |Cite
|
Sign up to set email alerts
|

ZnO flexible high voltage thin film transistors for power management in wearable electronics

Abstract: A ZnO-based flexible high voltage thin film transistor (f-HVTFT) is fabricated on a plastic substrate. The f-HVTFT shows a blocking voltage of 150 V, on-current of 170 μA, and off-current of 0.01 pA at a drain bias of 10 V. The maximum recoverable bending radius of the device reaches 11 mm, and the blocking voltage is larger than 120 V while it is under bending. The unique center-symmetric circular structure of the f-HVTFT is particularly useful to the wearable systems, which enable one to operate under bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Corbino TFT is a circular TFT consisting of inner and outer concentric ring electrodes, superior to the rectangular-shaped TFT in some properties. Due to the uniform electric field distribution in the channel region, Corbino TFT can potentially work at higher drain bias [28,29] and achieve better mechanical bending stability [30,31]. In addition, the output resistance of Corbino TFT behaves almost infinitely beyond pinch-off with the outer-ring electrode as drain [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corbino TFT is a circular TFT consisting of inner and outer concentric ring electrodes, superior to the rectangular-shaped TFT in some properties. Due to the uniform electric field distribution in the channel region, Corbino TFT can potentially work at higher drain bias [28,29] and achieve better mechanical bending stability [30,31]. In addition, the output resistance of Corbino TFT behaves almost infinitely beyond pinch-off with the outer-ring electrode as drain [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, research about high-voltage Corbino thin film transistors is limited [28,29]. Hong, et al, demonstrated magnesium zinc oxide (MZO) based Corbino HVTFT [28] and ZnO-based flexible Corbino HVTFT [29], which show a blocking voltage of 609 V and 150 V, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-voltage thin-film transistors (HV-TFTs) are critical components in the areas of photovoltaics [1][2][3], display [4][5][6][7], MEMS [8], x-ray detectors [9,10], actuators [11,12], and wearable devices [13], where high-voltage is necessary either to drive the corresponding building blocks or to harvest energy as an integral part of the power source. Gate/drain offset design has been adopted to increase the breakdown voltage of silicon, organic and oxide TFTs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%